Fifty shades of kale :50 fresh and satisfying recipes that are bound to please - Drew Ramsey (HarperWave, 2013)
"Author Drew Ramsay and Chef Jennifer Iserloh thought it would be fun to create a cookbook that merged two of the most popular trends sweeping America: bondage and kale. So they teamed up to quickly self-published an ebook: 50 Shades of Kale. And it turned out to be more than just fun-27,000 downloads later, they realized they were onto something. Now for the first time in hardcover, the book has been redesigned; re-shot with beautiful 4-color photography; and re-imagined with new content and recipes. The result is a gorgeous, sexy cookbook that offers readers 50 different ways to enjoy one of the healthiest vegetables in existence. Written with a playful nod to its inspiration, 50 Shades of Kale introduces kale as an enticing seductress whose nutrient powers and mouth-watering flavor make her one sought-after vegetable. The book offers a nutritional overview, kale cooking tips, and a tutorial on the various varieties of kale, as well as 50 delicious ways to have your kale and eat it too"--